French-derived Adverbs in Middle English - Kaskinen, Kirsi (My University, 2020)
This MA thesis examines the adverbs borrowed from French during the Middle English period (ca. from the 12th century to the end of the 15th century). The research material consists of 150 French-derived adverbs. They were collected from the Middle English Dictionary. The focus of the analysis was on the structure of the words. In addition, the aim was to obtain information when these adverbs were borrowed and how many of them are still in use in English. Mainly qualitative methods were used in this study. The results indicate that these adverbs are a very diverse group of words, including for example hybrid borrowings and loan blends as well as words which had gone through only minor changes during the borrowing process. Most of the words were borrowed during the 14th and 15th centuries. The majority of the adverbs are not in active use at present, but there are also some high-frequency words in Present-day English.
Keywords: Middle English language, French language, language contacts, loanwords